Is Family Planning Already Accepted by the Present Generation? Freshmen's View on Family Planning at University of North Sumatera, Medan ( Third Report ) - Amir Syarifuddin; Irwan Thahir; Berlian Hasibuan; Zakaria Siregar; Helena Siregar (Paediatrica Indonesiana, 1988)
A study on views of family planning among freshmen of University of North Sumatera, Medan was conducted for the third time in 1985. Questionnaires was distributed to 2245 freshmen of whom 1997 gave the response consisting of 1153 males and 844 females. The result showed that most of the freshmen (67,59%) planned to have only 2-3 children and get married at the ages of 25- 29 ye1rsÂ· 31,30% wished to have 2 sons and 1 daughter,Â· 79,75% had the opinion that son or daughter is the same, nearly all of them (97,75%) were planning to have a small family, whereas 34,95% planned to choose IUD for their family-planning method. We can conclude that family planning is well accepted by the present generation.